Deprivation and poor psychosocial support are key determinants of late antenatal presentation and poor fetal outcomes-a combined retrospective and prospective study. Issue 1 (December 2015) - Kapaya, Habiba; Mercer, Erin; Boffey, Francesca; Jones, Georgina; Mitchell, Caroline; Anumba, Dilly
Abstract Background Published guidelines emphasise the need for early antenatal care to promote maternal and neonatal health. Inadequate engagement with antenatal care is associated with adverse pregnancy outcomes including maternal death. The factors that influence the uptake and utilisation of maternity care services are poorly understood. We retrospectively explore a large maternity database of births in a large referral UK hospital to capture the socio-demographic factors that influence late pregnancy booking, and then prospectively compare the stress and social support status of consenting early and late-booking women. Methods Retrospective socio-demographic and clinical outcome data on 59, 487 women were collected from the maternity database record of births between 2002 and 2010 at the Jessop Wing Hospital, Sheffield UK. In a follow-on prospective survey between October 2012 and May 2013 a convenience cohort of early and late bookers for antenatal care were then studied using validated scales for fetomaternal attachment, stress and anxiety, and social support. Results In our retrospective study, pregnancy during the teenage years, higher parity, non-white ethnic background, unemployment and smoking were significantly associated with late access to antenatal services and poor fetal outcomes (P < 0.001). However, late booking per se did not predict adverse fetal outcomes, when socio-demographic factors were accounted for. A high index of multiple deprivation (IMD) score remained independently associated with late booking when confounding factors such as ethnicity and employment status were controlled for in the model (P = 0.03). Our prospective data demonstrated that women who book late were more likely to be unmarried (OR: 3.571, 95 % CI: 1.464–8.196, p = 0.005), of high parity (OR: 1.759, 95 % CI: 1.154–2.684, P = 0.009), and have lower social support than early bookers (P = 0.047). Conclusions Of the many complex sociocultural factors that influence the timing of maternal engagement with antenatal care, multiple deprivation and poor social support remain key factors. Improving access to prenatal care requires in-depth exploration of the relationship between maternal psychosocial health indices, social support mechanisms and engagement with antenatal care. Findings from these studies should inform interventions aimed at improving access to care.